The Relationship Between the Diet Served and The High Rate of Gastritis in Samarinda Police Detainees in East Kalimantan - Fhirawati, Fhirawati; Nurindahsari, Sri; Nugroho, Hadi (Jurnal EduHealth, 2022)
Gastritis is inflammation or bleeding of the gastric mucosa that is acute, chronic, diffuse or local. Gastritis is commonly known as "heartburn" or heartburn due to inflammation in the gastric mucosa which can cause swelling of the gastric mucosa to the detachment of the superficial mucosal epithelium which can become main cause of gastrointestinal disorders. The purpose of this study was to determine the relationship between the diet presented and the high rate of gastritis in Samarinda Police detainees in East Kalimantan. This type of quantitative analytic research with a retrospective study design, namely data collection starting from the effect or effect that has occurred, then from that effect is traced backwards about the cause or variables that influence the effect. The number of samples in this study were 97 male prisoners suffering from gastritis indications. The researcher draws the conclusion that most of the respondents' diets are in the bad category as many as 56 respondents (57.7%), Gastritis disease most of the respondents experience chronic gastritis as many as 52 respondents (53.6%), There is a relationship between diet and high rates of gastritis in Samarinda Polresta prison, East Kalimantan with a p value of 0.000 <0.05. From the results of this study, it is suggested that gastritis sufferers can carry out a good lifestyle and regular eating patterns according to the 3J guidelines, namely types of food, number of meals and hours of eating.